Application of Silver Ion High‐Performance Liquid Chromatography for Quantitative Analysis of Selected n‐3 and n‐6 PUFA in Oil Supplements. Issue 4 (3rd March 2016) - Czajkowska‐Mysłek, Anna; Siekierko, Urszula; Gajewska, Magdalena
Abstract: The aim of this study was to develop a simple method for simultaneous determination of selected cis/cis PUFA–LNA (18:2), ALA (18:3), GLA (18:3), EPA (20:5), and DHA (22:6) by silver ion high‐performance liquid chromatography coupled to a diode array detector (Ag‐HPLC‐DAD). The separation was performed on three Luna SCX Silver Loaded columns connected in series maintained at 10 °C with isocratic elution by 1 % acetonitrile in n ‐hexane. The applied chromatographic system allowed a baseline separation of standard mixture of n‐3 and n‐6 fatty acid methyl esters containing LNA, DHA, and EPA and partial separation of ALA and GLA positional isomers. The method was validated by means of linearity, precision, stability, and recovery. Limits of detection (LOD) for considered PUFA standard solutions ranged from 0.27 to 0.43 mg L −1 . The developed method was used to evaluate of n‐3 and n‐6 fatty acids contents in plant and fish softgel oil capsules, results were compared with reference GC‐FID based method.